Manufacturing and Evaluation of Mechanical, Morphological, and Thermal Properties of Reduced Graphene Oxide-Reinforced Expanded Polystyrene (EPS) Nanocomposites - Tomasz Rydzkowski; Kazimierz Reszka; Mieczysław Szczypiński; Michał Marek Szczypiński; Elżbieta Kopczyńska; Vijay Kumar Thakur (Advances in Polymer Technology)
The aim of the present study is to examine the effect of the addition of carbon nanoparticles (σsp2 hybridization) on the mechanical properties of foamed polystyrene. In this work, we focus on the study of the impact of compressive stress, tensile strength, bending strength, thermal conductivity ratio (λ), and water absorption of expanded polystyrene (EPS) reinforced with reduced graphene oxide and graphite. The results were compared with pristine EPS and reduced graphene oxide-reinforced EPS. All the nanocomposite specimens used for testing had a similar density. The study reveals that the nanocomposites exhibit different thermal conductivities and mechanical properties in comparison to pristine EPS. The enhancement in the properties of the nanocomposite could be associated with a more extensive structure of elementary cells of expanded polystyrene granules.